Increasing the number of universities and current situation of labour market in higher education - Qader, Mahdi A; Hasan, Ferman (Technium Social Sciences Journal, 2021)
In this analysis descriptive research is used, in order to illustrate a clear picture of the current situation of lebour marketing in higher education. The main aim of this review is to analyse and evaluate the current situation in the Kurdistan region of Iraq, also known as KRG (Kurdish Regional Government), in terms of higher education marketisation and employment opportunities for Higher education graduates. For this purpose. The influences of globalisation and neo- liberal ideology on the higher education sector were main points of consideration to explore the situation. Findings showed that the Kurdish government strongly follows neo-liberalism ideology in its strategies for Higher Education (H.E.) in order to move forward as a developing country. Consequently, the H.E. sector has experienced a significant expansion, especially through the introduction of private universities. However, the educational system which is in place in Kurdistan remains a work in progress. Whilst HE is considered a main priority of the regional government for developing the local young population and work opportunities are opening through foreign investors, graduate unemployment is high and remains an unsolved issue in the half public, half private university market situation.